Gene silencing in budding yeast - Gasser, Susan (Henry Stewart Talks, 2007)
Gene silencing: an epigenetic phenomenon, Chromatin remodeling: heterochromatin and euchromatin, Silent chromatin in budding yeast: mating-type loci, Silent information regulation: telomeric genes and Sir proteins
Updated at 2016/08/31